An Analysis of the Relation between Chastity and Actresses’ Popularity in TV Hit Feature Films' Female Cast - Mohsen Shakerinejad; Saeid Bagheri (Religion & Communication, 2019)
The research purpose is to examine the role of feature films' popular cast in shaping the audience’s attitude and behavior, since these characters can act as suitable models for people’s acceptance of chastity. The research method has been quantity analysis and its statistic population consisted of 36 hit feature films broadcast on TV. To analyze the data we used spss software together with descriptive and inductive statistics with 5% first type error. The results show that the specified films are lacking in appropriate characterization in regard to sticking to chastity, so they could not be taken as role models for the viewers. In general, one could say that TV hit feature films have failed to promote the culture of chastity by offering models.